Efficacy of Seed Priming With Cucurbitacin Phytonematicides Against Meloidogyne incognita on Pea - Mashela, Phatu William; Pofu, Kgabo Martha; Bopape-Mabapa, Moshibudi Paulina (Frontiers in Microbiology, 2022)
Cost and environment concerns of existing drench-application technologies of cucurbitacin phytonematicides resulted in conceptualization of priming-and-drying (PAD) technology of seeds with hypogeal germination. Preliminary observations suggested that PAD technology improved seed germination, plant growth and vigor in pea (Pisum sativa), with limited information on suppression of root-knot (Meloidogyne species) nematodes. Post-soaking pea seeds in geometric concentrations of Nemarioc-AL and Nemafric-BL phytonematicides, seedlings were raised in greenhouse and on microplot experiments during 2019 and validated in 2020. At 60 days after inoculation with 300 eggs + second-stage juveniles (J2) of M. incognita seasonal data were pooled. Gall rating, eggs in root and J2 in root versus Nemarioc-AL phytonematicide in greenhouse and on microplot exhibited negative quadratic relations, with models explained by 80-85% and 89-94% associations, respectively. Similarly, for the respective sites negative quadratic models for nematode variables versus Nemafric-BL phytonematicide were explained by 82-93% and 90-94% associations. In conclusion, pea seed remnants belowground gradually released cucurbitacins into the rhizosphere throughout the growing period, thereby suppressing nematode population densities, and therefore, PAD technology has the potential for assessment in largescale application of cucurbitacin phytonematicides for pea production.